Geophysical Diagnosis of Diversion Channel Infiltration in a Uranium Waste Rock Pile - Nascimento, Matheus Mistrinel Pacine Feitoza do [UNESP]; Moreira, César Augusto [UNESP]; Duz, Beatriz Guzzo [UNESP]; Silveira, Ana Júlia Traíba da [UNESP] (Springer Nature, 2022)
The Osamu Utsumi mine was the first to economically mine uranium ore in Brazil. During its operation, a river valley was buried for the construction of the waste rock pile. The original stream was diverted to the northwest side of the pile and has since flowed into a diversion channel devoid of basal waterproofing, while an acid mine drainage (AMD) source flows at the base of this waste rock pile. This research aims to evaluate the possible relationship between water infiltration of the diversion channel and the AMD resurgence at the base of the pile using electrical resistivity tomography and induced polarization. 2D inversion models and pseudo-3D maps allowed the recognition of low resistivity zones (< 100 Ω·m) with high chargeability areas (10 mV/V). Some of these low-resistivity areas have been interpreted as infiltration zones in segments of the diversion channel into the pile, and in one of them, the flow intercepts a high chargeability area interpreted as a sulfide-rich zone that is expected to contribute to AMD at the base of the pile. Understanding the hydrogeochemical process will help select effective actions to mitigate the generation of AMD at the mine, which is currently in the decommissioning phase.
Diagnóstico geofísico de la infiltración del canal de desvío en una pila de residuos de uranio
Keywords: Acid mine drainage; Brazil; Electrical resistivity tomography; Induced polarization; Uranium mine